2004
DOI: 10.1093/ndt/gfh039
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and urinary free 3-nitrotyrosine following cardiac angiography procedures with non-ionic radiocontrast media

Abstract: The present study provides indirect evidence that RCM administration in humans is associated with an increased production of 3-NT. Further studies are needed to ascertain whether oxygen- and nitrogen-derived radical species play a major role in the pathogenesis of RCM-associated nephrotoxicity in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Moreover, by means of HPLC with UV absorbance detection, similar to that used here (i.e. with a LOD of approximately 100 nM for 3-nitrotyrosine), 3-nitrotyrosine was measured in urine of patients administered with radiocontrast media at approximately 5.5 M or 11.3 mol/mmol creatinine [16]. These values are more than 1000 times higher than those measured by GC-tandem MS in the present study in healthy humans.…”
Section: Basal Levels Of 3-nitrotyrosine In Human Urinementioning
confidence: 47%
See 2 more Smart Citations
“…Moreover, by means of HPLC with UV absorbance detection, similar to that used here (i.e. with a LOD of approximately 100 nM for 3-nitrotyrosine), 3-nitrotyrosine was measured in urine of patients administered with radiocontrast media at approximately 5.5 M or 11.3 mol/mmol creatinine [16]. These values are more than 1000 times higher than those measured by GC-tandem MS in the present study in healthy humans.…”
Section: Basal Levels Of 3-nitrotyrosine In Human Urinementioning
confidence: 47%
“…Various groups reported that 3-nitrotyrosine is excreted in the urine of healthy humans [13][14][15][16]. Reported excretion rates and urinary concentrations of 3-nitrotyrosine vary between 60 nmol/day [15] and 248 nmol/day [13], i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The malondialdehydeto-creatinine ratio increased following contrast infusion, suggesting a link between contrast infusion and free radical generation. In a study investigating the effects of cardiac catheterization on the generation of reactive oxygen species, Fiaccadori and colleagues 30 measured urine and plasma levels of 3-nitrotyrosine(a marker of peroxynitrite generation from superoxide).Urinary 3-nitrotyrosine peaked after catheterization, but plasma levels remained elevated for up to 72 hours. However, in 193 lowrisk patients with normal renal function studied prospectively, there was no significant difference in the baseline serum levels of antioxidant compounds between those who did or did not develop renal failure after cardiac catheterization.…”
Section: E) Reperfusion and Reactive Oxygen Speciesmentioning
confidence: 99%
“…This nitrative stress is evidenced by the presence of nitrated protein tyrosine in the tissues (9,43) and by increased free 3-nitrotyrosine (NO2Tyr) in biological fluids (13,23). Experimental evidence has indicated that nitration of tyrosine residues in proteins may alter protein function and protein turnover and modify signal transduction processes (24).…”
mentioning
confidence: 99%